Redefining ideas and building scientific knowledge in high school through the study of water: An experience report - Andrade Silva Sattler, Eliza; Rocha Gonçalves, Paola; Mancini, Karina (Guará Journal, 2025)
This experience report describes the development and implementation of an activity on the properties of water aimed at developing the scientific method and stimulating and promoting student autonomy, placing the student as the main actor in constructing their learning. Thus, an investigative teaching sequence (IDS) was developed, organized in three stages, and implemented in a second-grade high school class at a state school in Vitória, Espírito Santo. In the first stage, students watched an introductory video on the topic to stimulate curiosity. Next, the class was divided into six groups, each given a guiding question to discuss, generate hypotheses, and research to suggest a practical experiment to develop that answers the question. In the third and final stage, students organized a mini-science fair in the classroom, where each group presented the guiding question and the experiment they developed. This IDS fostered in students the ability to work collaboratively, learn through experience, student leadership, and scientific literacy.